2002
DOI: 10.1094/pdis.2002.86.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Incidence, and Severity of Sorghum Diseases in Western Kenya

Abstract: To assess the prevalence and severity of sorghum diseases in western Kenya, a 2-year survey was conducted (July 1995 and 1996), in 91 and 109 farmers' fields, respectively. Fields were generally <0.5 ha and production environment ranged from warm-humid to warm-semi-arid. Fourteen foliar and six panicle diseases were observed, with limited variation in disease prevalence and severity between the 2 years. The most common foliar diseases observed were (in decreasing order of prevalence) oval leaf spot (Ramulis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 11 publications
1
44
0
Order By: Relevance
“…Bigirwa et al (1998) and Adipala et al (1999) reported low prevalence of downy mildew disease with 10% disease incidence (Bigirwa et al 1998) with isolated distribution pattern of the disease for different cropping seasons. Similarly, low impact of the disease was reported in Nigeria (Ngugi et al, 2002), Zimbabwe, Zambia, Mozambique and Rwanda . Contrary to these earlier reports on the disease distribution and prevalence (EPPO, 2014), this study however showed a significantly high disease incidence and severity pattern with a wider distribution pattern across ten agroecological zones.…”
Section: Results:-mentioning
confidence: 85%
See 1 more Smart Citation
“…Bigirwa et al (1998) and Adipala et al (1999) reported low prevalence of downy mildew disease with 10% disease incidence (Bigirwa et al 1998) with isolated distribution pattern of the disease for different cropping seasons. Similarly, low impact of the disease was reported in Nigeria (Ngugi et al, 2002), Zimbabwe, Zambia, Mozambique and Rwanda . Contrary to these earlier reports on the disease distribution and prevalence (EPPO, 2014), this study however showed a significantly high disease incidence and severity pattern with a wider distribution pattern across ten agroecological zones.…”
Section: Results:-mentioning
confidence: 85%
“…These loses occur in tropical lowland, subtropical, mid-altitude, and highland environments when the disease is left uncontrolled (Jeffers et al, 2000). Although empirical information on distribution of SDM in sorghum is limited in Uganda, reports on severity and distribution are available from neighboring countries of Kenya (Ngugi et al, 2002, EPPO, 2014 and Tanzania and Burundi (EPPO, 2014). Limited information and research on the disease coupled with farmers' lack of knowledge in the preventive and control mechanisms of the disease poses a severe threat to the production of the crop.…”
mentioning
confidence: 99%
“…Even though annual rainfall is similar across the administrative districts, the Okavango Delta is located in the Ngamiland district, which may contribute to the higher frequency of accessions showing anthracnose resistance from this region. Several studies have reported that annual rainfall is an important weather variable influencing disease severity (Néya & Le Normand 1998;Hess et al 2002;Ngugi et al 2002); however, other climatic conditions that would contribute to a greater leaf wetness period would also affect disease severity (Pande et al 1994) and may contribute to the variation observed between regions. Pathogenic diversity may also occur between regions (Marley et al 2001) and could contribute to the observed diversity in disease response for the germplasm from the different districts.…”
Section: Discussionmentioning
confidence: 99%
“…The Mopti region receives less than 800 mm of annual rainfall (Hess et al, 2002). Several studies have indicated that anthracnose infection severity is greater in regions receiving higher annual rainfall (Hess et al, 2002;Néya and Le Normand, 1998;Ngugi et al, 2002); thus, selection pressure may favor a higher frequency of anthracnose resistant germplasm in these wetter regions. Presumably, sorghum landraces from regions receiving low annual rainfall, such as the Mopti region, would show greater disease severity and a lower frequency of anthracnose resistant germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…in Kabat and Bubák) is the fungal pathogen responsible for sorghum anthracnose (Crouch et al, 2006) and was first reported in Togo, West Africa in 1902 (Thakur and Mathur, 2000). The disease occurs worldwide, but is more commonly observed in tropical or subtropical environments where frequent rainfall, high relative humidity and warm temperatures enhance the development and spread of the disease (Casela et al, 2001;Hess et al, 2002;Marley et al, 2001;Néya and Le Normand, 1998;Ngugi et al, 2002;Thakur and Mathur, 2000;Thomas et al, 1996;Valério et al, 2005). In the United States, anthracnose is more prevalent in the Southern Plains and Southeastern States (Rosewich et al, 1998;Cardwell et al, 1989).…”
Section: Introductionmentioning
confidence: 99%